studi penggunaan superkapasitor sebagai media penyimpan energi - NURHASMIA NURHASMIA (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2021)
Supercapacitor is an alternative media for electrical storage, this media is different from conventional battery and capacitor, supercapacitor is capacitor with bigger capacitance than battery. The purpose of this research is to find out how long it takes in the process of charging and discharging the voltage on the supercapacitor, by using 3 methods of charging and discharging namely charging and discharging singly, series and parallel. From the results obtained, the time of charging on single pair supercapacitor needs 5 hours and the time for discharging supercapacitor needs 11 hours and thirty minutes. The process on two supercapacitors in series, the time to charging needs 27 hours and the time to discharging needs 12 hours, while the two parallel supercapacitors needs 5 hours to fill and needs 15 hours to empty the supercapacitor.